Method for manufacturing molded article and adhesive molded article

By controlling the temperature drop rate during the manufacturing of PTFE and thermal-melted tetrafluoroethylene polymer objects, the method addresses uneven surfaces and adhesiveness issues, resulting in dense, crack-resistant objects with improved heat and electrical properties.

JP2025016014APending Publication Date: 2025-01-31AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023119004
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

The molded objects produced from existing tetrafluoroethylene (PTFE) dispersions exhibit uneven fiber-like surfaces and adhesiveness issues, leading to potential cracking and inadequate properties like heat resistance and electrical characteristics.

Method used

A controlled temperature drop method is employed during the manufacturing process, where polytetrafluoroethylene (PTFE) and thermal-melted tetrafluoroethylene polymer particles are mixed with a liquid medium, heated, and cooled at a rate of less than 5 °C/min to form a dense, fiber-like surface with enhanced adhesiveness, reducing the likelihood of cracks and improving heat resistance, weather resistance, and electrical characteristics.

Benefits of technology

The method results in molded objects with a fiber-like surface material based on PTFE fibrils, exhibiting excellent adhesiveness, heat resistance, weather resistance, and electrical characteristics while minimizing cracking, and enhancing mechanical properties like bending resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a method for manufacturing a molded article which contains polytetrafluoroethylene and a specific tetrafluoroethylene-based polymer, has fibrous surface physical property and adhesion based on a fibril structure of the polytetrafluoroethylene, prevents generation of cracks and is excellent in heat resistance, weather resistance and electric characteristics, and is dense.SOLUTION: A manufacturing method includes arranging a dispersion liquid containing polytetrafluoroethylene particles, heat-meltable tetrafluoroethylene-based polymer particles, and a liquid medium, heating the substances within the temperature range of higher than a melting temperature of the tetrafluoroethylene-based polymer, and obtaining a molded article containing the polytetrafluoroethylene and the tetrafluoroethylene-based polymer, and lowers the temperature of the molded article to at least the melting temperature of the tetrafluoroethylene-based polymer or lower at a temperature lowering rate of lower than 5°C / min, after heating.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a molded article. In particular, the present invention relates to a method for producing a molded article, such as a laminate or a prepreg, containing polytetrafluoroethylene and a heat-fusible tetrafluoroethylene-based polymer. [Background technology]

[0002] Tetrafluoroethylene-based polymers such as polytetrafluoroethylene (PTFE), copolymers of tetrafluoroethylene and perfluoro(alkyl vinyl ether) (PFA), and copolymers of tetrafluoroethylene and hexafluoropropylene (FEP) have excellent physical properties such as release properties, electrical properties, water and oil repellency, chemical resistance, weather resistance, and heat resistance, and these physical properties are utilized in a variety of industrial applications. A dispersion in which particles of a tetrafluoroethylene-based polymer are dispersed in a liquid dispersion medium is useful because, when applied to the surface of various substrates, the physical properties of the tetrafluoroethylene-based polymer can be imparted to the surface. Patent Document 1 proposes a dispersion containing a powder of a first polymer having a unit based on tetrafluoroethylene and an oxygen-containing polar group, and a powder of a second polymer containing a unit based on fluoroolefin, the first polymer and the second polymer being contained in a predetermined content ratio. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2020 / 004339 Summary of the Invention [Problem to be solved by the invention]

[0004] The molded article obtained from the dispersion proposed in Patent Document 1 has fibrous surface properties and adhesiveness based on the fibril structure of polytetrafluoroethylene. As a result of more detailed investigation into the properties and physical properties of the molded article obtained from the dispersion proposed in Patent Document 1, the present inventors found that the heat-fusible tetrafluoroethylene-based polymer may be locally exposed or unevenly distributed on the surface of the molded article, and that there is room for improvement in the fibrous surface properties of the molded article. Therefore, the present inventors have focused on the process of coating a dispersion liquid containing particles of polytetrafluoroethylene and particles of a heat-meltable tetrafluoroethylene-based polymer and a liquid dispersion medium on the surface of a substrate, and baking the polymer.As a result, they have found that when the temperature drop state after baking the polymer, specifically the temperature drop rate, is controlled to a specific condition, a dense molded product can be obtained that has fibrous surface properties and adhesiveness based on the fibril structure of polytetrafluoroethylene, is unlikely to crack even when a thick layer is formed, and has excellent heat resistance, weather resistance, electrical properties, etc., and have arrived at the present invention. An object of the present invention is to provide a production method capable of forming a dense molded article which contains polytetrafluoroethylene and a specific tetrafluoroethylene-based polymer, has fibrous surface properties and adhesiveness based on the fibril structure of polytetrafluoroethylene, is less susceptible to cracking, and has excellent heat resistance, weather resistance, electrical properties, etc. [Means for solving the problem]

[0005] The present invention has the following aspects. [1] A method for producing a molded product, comprising disposing a dispersion containing polytetrafluoroethylene particles, particles of a heat-fusible tetrafluoroethylene-based polymer, and a liquid medium, and heating the dispersion in a temperature range above the melting temperature of the tetrafluoroethylene-based polymer to obtain a molded product containing the polytetrafluoroethylene and the tetrafluoroethylene-based polymer, and further comprising, after the heating, lowering the temperature at a rate of less than 5°C / min to at least the melting temperature of the tetrafluoroethylene-based polymer. [2] The production method according to [1], wherein the melting temperature of the tetrafluoroethylene polymer is 230 to 320°C. [3] The method according to [1] or [2], wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer having a carbonyl group-containing group. [4] The method according to any one of [1] to [3], wherein the polytetrafluoroethylene particles have an average particle size of 0.01 to 10 μm, the tetrafluoroethylene-based polymer particles have an average particle size of 0.05 to 50 μm, and the former has an average particle size equal to or smaller than the latter. [5] The method according to any one of [1] to [4], wherein the content of the tetrafluoroethylene polymer particles in the dispersion is 5 mass % or more relative to the polytetrafluoroethylene particles. [6] The method according to any one of [1] to [5], wherein after the heating, the temperature-lowering rate of less than 5° C. / min is maintained until the temperature reaches at least [the melting temperature of the tetrafluoroethylene-based polymer −10° C.]. [7] The method according to any one of [1] to [6], wherein the dispersion further contains a surfactant. [8] The method according to any one of [1] to [7], wherein the dispersion further contains an inorganic filler. [9] The method according to any one of [1] to [8], wherein the liquid medium is at least one selected from the group consisting of water, amides, ketones and esters.

[10] The method according to any one of [1] to [9], wherein the dispersion is applied and disposed on a surface of a substrate to form a laminate having a substrate layer and a polymer layer.

[11] The method of

[10] , wherein the polymer layer has a thickness of 25 μm or more.

[12] The method according to any one of [1] to [9], further comprising impregnating a fiber substrate with the dispersion to form an impregnated substrate in which the fiber substrate is impregnated with the polymer.

[13] An adhesive molded article comprising polytetrafluoroethylene and a heat-fusible tetrafluoroethylene polymer, the adhesive molded article having substantially the entire surface with fibrous surface properties. Effect of the Invention

[0006] According to the present invention, there is provided a production method capable of forming a dense molded article which contains polytetrafluoroethylene and a heat-fusible tetrafluoroethylene-based polymer, has fibrous surface properties and adhesiveness based on the fibril structure of polytetrafluoroethylene, is less susceptible to cracking, and has excellent heat resistance, weather resistance, electrical properties, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The following terms have the following meanings. "Average particle size (D50)" is the cumulative 50% volumetric diameter of a particle or filler determined by a laser diffraction / scattering method. In other words, the particle size distribution is measured by a laser diffraction / scattering method, the total volume of the particle or filler group is set as 100%, a cumulative curve is calculated, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of particles or fillers is determined by dispersing the particles in water and analyzing them by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). The "D90" of a particle or filler is the volume-based cumulative 90% diameter of the particle or filler, measured in the same manner as D50 above. "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). "Glass transition temperature (Tg)" is a value measured by analyzing a polymer using the dynamic mechanical analysis (DMA) method. The "viscosity" is determined by measuring the dispersion using a Brookfield viscometer at 25° C. and 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is calculated. The "thixotropy ratio" is a value calculated by dividing the viscosity η1 of the dispersion measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement was repeated three times, and the average value of the three measurements was used. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."

[0008] The manufacturing method of the present invention (hereinafter also referred to as "this method") is a manufacturing method for a molded product, which comprises disposing a dispersion (hereinafter also referred to as "this dispersion") containing particles of polytetrafluoroethylene (PTFE) (hereinafter also referred to as "PTFE particles"), particles of a heat-fusible tetrafluoroethylene-based polymer (hereinafter also referred to as "F polymer") (hereinafter also referred to as "F particles"), and a liquid medium, and heating the dispersion in a temperature range above the melting temperature of the F polymer to obtain a molded product containing the PTFE and the F polymer, and then cooling the product at a rate of less than 5°C / min to at least the melting temperature of the F polymer after the heating. According to this method, it is possible to form a dense molded product that contains PTFE and F polymer, has fibrous surface properties and adhesiveness based on the fibril structure of PTFE, is less likely to crack, and has excellent heat resistance, weather resistance, electrical properties, etc. The reason for this is not necessarily clear, but is thought to be as follows.

[0009] In this method, the coating layer formed by disposing the present dispersion is heated in a predetermined temperature range to remove the liquid medium, and the PTFE particles and F polymer particles are baked to obtain a molded product containing PTFE and F polymer. After heating, the temperature is lowered at a rate of less than 5°C / min to at least the melting temperature of the F polymer. That is, by controlling the temperature lowering rate after baking the polymer within a predetermined range, the temperature is lowered slowly, and the molten F polymer is maintained in a fluid or softened state, so that rapid solidification is easily suppressed. It is presumed that such suppression of rapid solidification easily promotes the interaction between PTFE and the F polymer, and prevents the F polymer from bleeding out on the surface of the molded product and being locally exposed or unevenly distributed. As a result, it is considered that a molded product having dense PTFE fibrous surface properties was obtained without the F polymer bleeding out on the surface. Thus, the molded product obtained by this method has fibrous surface properties based on the fibril structure of PTFE over the entire surface, and is also adhesive, dense and resistant to cracking, and has excellent heat resistance, weather resistance, electrical properties, etc. Furthermore, the low friction of the molded product surface based on the physical properties of PTFE is easily maintained. Therefore, this method is particularly useful when it is desired to incorporate a sufficient amount of F polymer into a molded product and improve mechanical properties such as bending property in addition to the above-mentioned physical properties.

[0010] In the present invention, the F polymer is a heat-meltable polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE"). Here, the heat-meltable polymer means a polymer having a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The melting temperature of the F polymer is preferably 230° C. or higher, more preferably 260° C. or higher. The melting temperature of the F polymer is preferably 320° C. or lower, more preferably 315° C. or lower. In this case, the present dispersion used in the present method tends to have excellent processability, and molded products such as polymer layers formed from the present dispersion tend to have excellent heat resistance. The F polymer may be used alone or in combination of two or more kinds.

[0011] The glass transition temperature of the F polymer is preferably 60° C. or higher, more preferably 75° C. or higher. The glass transition temperature of the F polymer is preferably 120° C. or lower, more preferably 100° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a mixture for wetting tension testing (manufactured by Wako Pure Chemical Industries, Ltd.) specified in JIS K 6768 on a flat plate made of the F polymer.

[0012] F polymer is preferably a polymer containing TFE unit and ethylene-based unit (ETFE), a polymer containing TFE unit and propylene-based unit, a polymer containing TFE unit and perfluoro(alkyl vinyl ether) (PAVE)-based unit (PAVE unit) (PFA), a polymer containing TFE unit and hexafluoropropylene-based unit (FEP), more preferably PFA and FEP, and even more preferably PFA. These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.

[0013] At least one of the F polymers preferably has an oxygen-containing polar group, more preferably has a hydroxyl- or carbonyl-containing group, and even more preferably has a carbonyl-containing group. In this case, the dispersion used in the present method tends to have excellent dispersibility, and the molded product such as a polymer layer formed from such a dispersion tends to have excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant, and low dielectric loss tangent). The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), a formyl group, a halogenoformyl group, a urethane group (-NHC(O)O-), a carbamoyl group (-C(O)-NH2), a ureido group (-NH-C(O)-NH2), an oxamoyl group (-NH-C(O)-C(O)-NH2) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue. When the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6 The number of oxygen-containing polar groups per unit is preferably 50 to 5000, more preferably 100 to 3000. The number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.

[0014] The oxygen-containing polar group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment.

[0015] The heat-meltable F polymer is preferably a polymer (1) that does not have an oxygen-containing polar group and contains TFE units and PAVE units, and contains 2.0 to 5.0 mol% of PAVE units based on the total units, or a polymer (2) that contains TFE units and PAVE units and has an oxygen-containing polar group. If such an F polymer is used, spherulites with a relatively small radius are easily formed. Therefore, the adhesiveness of the molded product formed from this dispersion is easily improved.

[0016] It is more preferable that the polymer (1) is composed only of TFE units and PAVE units, and contains more than 2.5 mol % and 5.0 mol % or less of PAVE units based on the total units. In addition, the fact that the polymer (1) does not have an oxygen-containing polar group means that the number of the oxygen-containing polar groups is 1×10 of the carbon atoms constituting the polymer main chain. 6 This means that the number of oxygen-containing polar groups contained in the polymer is less than 50 per unit area. The lower limit of the number of oxygen-containing polar groups is 1. The polymer (1) may be produced by using a polymerization initiator or a chain transfer agent that does not generate an oxygen-containing polar group as a terminal group of the polymer chain, or by fluorinating an F polymer having an oxygen-containing polar group (such as an F polymer having an oxygen-containing polar group derived from a polymerization initiator at the terminal group of the polymer main chain). Examples of the fluorination method include a method using fluorine gas (see JP 2019-194314 A, etc.).

[0017] The polymer (2) is preferably an F polymer having a carbonyl group-containing group containing TFE units and PAVE units, more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in this order in an amount of 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol% relative to the total units. Specific examples of such F polymers include the polymers described in WO 2018 / 16644. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.

[0018] The average particle size (D50) of the F particles is preferably 0.05 μm or more, more preferably 0.5 μm or more, and even more preferably 1.0 μm or more. The D50 of the F particles is preferably 50 μm or less, more preferably 10 μm or less, and even more preferably 6 μm or less. Furthermore, the D90 of the F particles is preferably 6 to 9 μm. In this case, the present dispersion used in the present invention is likely to have excellent dispersibility and processability, and the molded product such as a polymer layer formed from the present dispersion is likely to have excellent heat resistance, electrical properties (low linear expansion coefficient, low dielectric constant, and low dielectric tangent), adhesiveness, and mechanical properties such as bending resistance. The specific surface area of ​​F particles is 1 to 25 m 2 / g is preferred. The F particles may be crushed particles obtained by mechanically crushing a heat-fusible tetrafluoroethylene polymer using a dry jet mill or the like.

[0019] The F particles are particles containing an F polymer, and preferably consist of an F polymer. The F particles are more preferably particles of an F polymer, which is polymer (2), having a melting temperature of 230 to 320° C. In this case, aggregation of the F particles is easily suppressed. The F particles may contain a resin or an inorganic compound other than the F polymer, may form a core-shell structure with an F polymer as the core and a resin or inorganic compound other than the F polymer as the shell, or may form a core-shell structure with an F polymer as the shell and a resin or inorganic compound other than the F polymer as the core. Here, examples of the resin other than the F polymer include aromatic polyester, polyamideimide, polyimide, and maleimide, and examples of the inorganic compound include silica and boron nitride. One type of F particle may be used, or two or more types of F particles may be used.

[0020] In the present invention, PTFE may be either non-thermofusible or heat-fusible, and is preferably non-thermofusible. The average particle size (D50) of the PTFE particles contained in the present dispersion is preferably 0.01 μm or more, more preferably 0.1 μm or more, and preferably 10 μm or less, more preferably 1 μm or less.

[0021] In the present dispersion, it is particularly preferred that the average particle size (D50) of the PTFE particles is 0.01 to 1 μm, the average particle size (D50) of the F particles is 0.05 to 10 μm, and the D50 of the PTFE particles is equal to or less than the D50 of the F particles. In this case, the present method makes it easy to obtain from the present dispersion a dense molded product that has fibrous surface properties and adhesiveness based on the fibril structure of PTFE, is less susceptible to cracking, and has excellent heat resistance, weather resistance, electrical properties, etc.

[0022] The content of F particles in the present dispersion is preferably 5% by mass or more relative to the PTFE particles, and is preferably 35% by mass or less, more preferably 25% by mass or less, relative to the PTFE particles. In the present dispersion, the content of the PTFE particles is preferably 75 to 95 mass % based on the total amount of the PTFE particles and the F particles. As the F particles constituting the present dispersion, particles of polymer (2) having a melting temperature of 230 to 320°C and an oxygen-containing polar group are more preferred. In this case, the aggregation suppression effect of the F particles and the retention effect due to the fibrillation of non-thermofusible PTFE are balanced, and the dispersibility of the present dispersion used in the present method is likely to be improved. In addition, in a molded product such as a polymer layer formed therefrom, the molded product surface is likely to have fibrous surface properties based on the fibril structure of PTFE, and a dense molded product that is less likely to crack and has excellent heat resistance, weather resistance, electrical properties, etc. is likely to be obtained. In addition, the bending resistance of the obtained molded product is improved, and the electrical properties of PTFE are also likely to be highly expressed.

[0023] The liquid medium constituting the present dispersion is preferably a compound that is liquid at 25° C. under atmospheric pressure and has a boiling point of 50 to 240° C. One type of liquid medium may be used, or two or more types may be used. When two types of liquid media are used, the two types of liquid media are preferably compatible with each other. The liquid medium is preferably at least one selected from the group consisting of water, amides, ketones and esters. Examples of amides include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone. Examples of the ketone include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone. Examples of the ester include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, γ-butyrolactone, and γ-valerolactone. In this method, it is preferable to use water or a mixture of water and the above-mentioned water-soluble amides, ketones and esters having a water content of 80% by mass or more as the liquid medium, and it is more preferable to use water. The content of the liquid medium in the present dispersion is preferably 15% by mass or more, more preferably 25% by mass or more, and is preferably 65% ​​by mass or less, more preferably 50% by mass or less.

[0024] The dispersion may further contain a surfactant. The surfactant is preferably a nonionic surfactant. Examples of the nonionic surfactant include glycol-based surfactants, acetylene-based surfactants, and silicone-based surfactants. Among these, nonionic surfactants having a hydroxyl group in the hydrophilic moiety are preferred, and polyoxyalkylene-modified dimethylsiloxanes having a polyoxyalkylene structure in the hydrophilic moiety and a polydimethylsiloxane structure in the hydrophobic moiety are more preferred. The nonionic surfactant may be used alone or in combination of two or more kinds. Specific examples of nonionic surfactants include the "Ftergent" series manufactured by Neos, the "Surflon" series manufactured by AGC Seimi Chemical Co., Ltd., the "Megafac" series manufactured by DIC Corporation, the "Unidyne" series manufactured by Daikin Industries, Ltd., "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", and "BYK-3456" manufactured by BYK Japan, "KF-6011" and "KF-6043" manufactured by Shin-Etsu Chemical Co., Ltd., and the "Tergitol" series manufactured by Dow Chemical Co., Ltd. (such as "Tergitol TMN-100X"). When the present dispersion contains a surfactant, the content thereof is preferably 0.01 to 10% by mass based on the total amount of the present dispersion.

[0025] The present dispersion may further contain an inorganic filler, in which case the formed product such as a coating film (polymer layer) formed from the present dispersion is likely to have excellent electrical properties and low linear expansion. The shape of the inorganic filler is not particularly limited, and may be, for example, spherical, acicular (fibrous), or plate-like. Examples of inorganic fillers include silicon compounds such as quartz powder, silica, wollastonite, talc, silicon nitride, silicon carbide, and mica; nitrogen compounds such as boron nitride and aluminum nitride; metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide; carbon fibers; carbon allotropes such as graphite, graphene, and carbon nanotubes; and metals such as silver and copper. The inorganic filler may be used alone or in combination of two or more kinds. The inorganic filler preferably has a D50 of 0.1 to 20 μm. The surface of the inorganic filler may be treated with a silane coupling agent. When the present dispersion contains an inorganic filler, the content thereof is preferably 1 to 25% by mass based on the entire present dispersion.

[0026] The present dispersion may further contain other resins different from PTFE and F polymer. Such other resins may be contained in the present dispersion as non-hollow particles, or may be dissolved or dispersed in the liquid medium constituting the present dispersion. Examples of other resins include polyester resins such as liquid crystalline aromatic polyesters, polyimide resins, polyamideimide resins, epoxy resins, maleimide resins, urethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. The other resin is preferably an aromatic polymer, more preferably at least one aromatic imide polymer selected from the group consisting of aromatic polyimide, aromatic polyamic acid, aromatic polyamideimide, and a precursor of aromatic polyamideimide. The aromatic polymer is preferably contained in the dispersion as a varnish dissolved in a liquid medium. When the present dispersion further contains another resin, the content of the other resin relative to the F particles is preferably 1 to 25% by mass.

[0027] The dispersion may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, and a flame retardant.

[0028] The viscosity of the present dispersion is preferably 10 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the present dispersion is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less. In this case, the present dispersion has excellent coatability and is easy to form a molded product such as a coating film (polymer layer) of any thickness. In addition, the present dispersion having a viscosity in this range is easy to highly express the physical properties of the F polymer in the molded product formed from it. The thixotropy ratio of the present dispersion is preferably 1.0 to 3.0, in which case the present dispersion has excellent coatability and homogeneity, and is likely to produce a denser molded product.

[0029] The present dispersion is obtained by mixing PTFE particles, F particles, a liquid medium, and, if necessary, a surfactant, an inorganic filler, other resins, additives, etc. The present dispersion may be obtained by mixing the PTFE particles, F particles, and a liquid medium all at once, or by mixing them in several separate batches. When a surfactant, inorganic filler, other resins, or additives are further mixed, the mixing order is not particularly limited. They may be mixed with the PTFE particles or F particles in advance and then mixed with the liquid medium, they may be added to the liquid medium in advance and then mixed with the PTFE particles and F particles, or they may be mixed when the liquid medium is added to the PTFE particles and F particles. Alternatively, a dispersion containing PTFE particles, a liquid medium, and optionally a surfactant, etc., and a dispersion containing F particles, a liquid medium, and optionally a surfactant, etc., may be separately prepared, and then these may be mixed to obtain the present dispersion. Examples of mixing devices for obtaining the present dispersion include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.

[0030] A specific embodiment of the present method is to form a laminate having a substrate layer and a polymer layer by applying the present dispersion onto the surface of the substrate. In other words, the present dispersion is applied onto the surface of the substrate to form a laminate having a substrate layer and a polymer layer as a molded product. The method for applying the present dispersion to the surface of the substrate includes a coating method, a droplet ejection method, and a dipping method, and is preferably a roll coating method, a knife coating method, a bar coating method, a die coating method, or a spray method. The present dispersion is applied to the substrate to first form a coating layer made of the present dispersion on the surface of the substrate.

[0031] The substrate is preferably a heat-resistant substrate. Examples of the heat-resistant substrate include metal substrates such as metal foils of copper, nickel, aluminum, titanium, and alloys thereof; heat-resistant resin films such as polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystal polymers such as liquid crystal polyester, and tetrafluoroethylene-based polymers other than F polymers such as polytetrafluoroethylene; prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates such as silicon carbide, aluminum nitride, and silicon nitride; and glass substrates. Among these, the heat-resistant substrate is preferably a resin film of any one of polyimide, liquid crystal polymer and polytetrafluoroethylene, and a polyimide film is more preferable.

[0032] The shape of the substrate may be flat, curved, or uneven, and may be any of a foil, plate, film, and fiber shape. The ten-point average roughness of the surface of the substrate is preferably 0.01 to 0.05 μm. The surface of the substrate may be subjected to a surface treatment with a silane coupling agent or a plasma treatment.

[0033] The substrate having the coating layer is heated to remove the liquid medium constituting the present dispersion. The heating for removing the liquid medium is preferably performed at 100 to 200°C for 0.1 to 30 minutes. In this heating, the liquid medium does not need to be completely removed, and it is sufficient to remove it to the extent that the layer formed by the packing of the PTFE particles and the F particles can maintain a self-supporting film. In addition, when heating, air may be blown to promote removal of the dispersion medium by air drying. Next, the F polymer is baked by heating in a temperature range above the melting temperature of the F polymer, to obtain a laminate having a polymer layer (hereinafter also referred to as "F layer") containing the F polymer on the surface of the substrate. Specifically, the heating for baking the F polymer is preferably performed at 340 to 400°C for 0.1 to 30 minutes. The heating device for each of the above heating methods may be an oven or a ventilated drying furnace. The heat source in the device may be a contact type heat source (hot air, hot plate, etc.) or a non-contact type heat source (infrared rays, etc.). In this method, each heating may be carried out under normal pressure (atmospheric pressure) or under reduced pressure. The atmosphere during each heating step may be either an air atmosphere or an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.).

[0034] In this method, after heating for baking the F polymer, the temperature is lowered at a rate of less than 5°C / min to at least the melting temperature of the F polymer, thereby obtaining a laminate having a substrate layer made of a substrate and an F layer. The cooling rate is preferably 1° C. / min or more. From the viewpoint of further promoting the above-mentioned assumed mechanism and further achieving the effects of the present invention, it is preferable to maintain a cooling rate of less than 5° C. / min until the temperature reaches at least [melting temperature of F polymer−10° C.] after the heating, it is more preferable to maintain a cooling rate of less than 5° C. / min until the temperature reaches [melting temperature of F polymer−60° C.], and it is even more preferable to maintain a cooling rate of less than 5° C. / min until the glass transition temperature of F polymer. The temperature drop rate can be controlled, for example, by using a temperature control function associated with the above-mentioned oven or ventilated drying furnace as the heating device. For example, after maintaining a cooling rate of less than 5°C / min to at least [the melting temperature of F polymer - 10°C], the laminate can be obtained by cooling in air or by appropriate cooling such as water cooling without controlling the cooling temperature. More specifically, it is preferable to maintain a temperature drop rate of less than 5° C. / min from [melting temperature of F polymer−10° C.] to [melting temperature of F polymer−60° C.].

[0035] The F layer is formed through the steps of disposing the dispersion on the substrate, heating, and lowering the temperature as specified above. This series of steps may be repeated two or more times. Alternatively, the present dispersion may be applied to the surface of a substrate to obtain a coating layer, and the liquid medium may be removed by heating. The surface may then be further coated with the present dispersion, and after heating to bake the F polymer, the temperature may be lowered at a rate of less than 5°C / min to at least the melting temperature of the F polymer to form an F layer. Alternatively, the present dispersion may be applied to the surface of a substrate to obtain a coating layer, an F layer may be formed by heating, the present dispersion may be further applied to the surface of the F layer to form a coating layer, and a second F layer may be formed by heating. After heating to form the second F layer, the temperature may be lowered at a rate of less than 5°C / min to at least the melting temperature of the F polymer to form an F layer.

[0036] The dispersion may be disposed on only one surface of the substrate, or on both surfaces of the substrate, in which case a laminate having the substrate and the F layer on one surface of the substrate is obtained, and in which case a laminate having the substrate and the F layer on both surfaces of the substrate is obtained. Suitable specific examples of the laminate include a metal-clad laminate having a metal foil and an F layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and an F layer on both surfaces of the polyimide film.

[0037] The surface of the F layer obtained by this method is likely to have fibrous surface properties based on the fibril structure of PTFE. The thickness of the F layer is preferably 25 μm or more, more preferably 30 μm or more, and even more preferably 50 μm or more. The thickness of the F layer is preferably 300 μm or less. The dielectric constant of the F layer is preferably 2.4 or less, more preferably 2.0 or less. Also, the dielectric constant is preferably greater than 1.0. The dielectric tangent of the F layer is preferably 0.0022 or less, more preferably 0.0020 or less. Also, the dielectric tangent is preferably greater than 0.0010. The thermal conductivity of the F layer is preferably 1 W / m·K or more, more preferably 3 W / m·K or more. The thermal conductivity of the F layer means the thermal conductivity in the in-plane direction of the F layer.

[0038] The linear expansion coefficient of the F layer is preferably 100 ppm / ° C. or less, more preferably 80 ppm / ° C. or less. The lower limit of the linear expansion coefficient of the F layer is 30 ppm / ° C. The linear expansion coefficient means a value obtained by measuring the linear expansion coefficient of a test piece in the range of 25° C. or more and 260° C. or less according to the measurement method specified in JIS C 6471:1995. The peel strength between the F layer and the base layer is preferably 10 N / cm or more, more preferably 15 N / cm or more, and is preferably 100 N / cm or less. Furthermore, by separating the base layer from such a laminate, a film or sheet containing PTFE and an F polymer, which has fibrous surface properties based on the fibril structure of PTFE, can be obtained.

[0039] Another specific embodiment of the present method is to impregnate a fiber substrate with the present dispersion and form an impregnated substrate in which the fiber substrate is impregnated with a polymer. In other words, this embodiment is to impregnate a fiber substrate with the present dispersion and form a prepreg as a molded product. In this specification, the term "prepreg" is used to include various embodiments of impregnated substrates in which a fiber substrate is impregnated with a polymer, which are also called polymer-reinforced fiber substrates, fiber-reinforced films, impregnated woven fabrics, etc., in the sense of being positioned as molded products. The fiber substrate is preferably a substrate made of reinforcing fibers. Examples of reinforcing fibers include inorganic fibers such as carbon fibers, graphite fibers, glass fibers, silicon carbide fibers, silicon nitride fibers, alumina fibers, silicon carbide fibers, and boron fibers; metal fibers such as aluminum fibers, brass fibers, and stainless steel fibers; and organic fibers such as aromatic polyamide fibers, polyaramid fibers, polyparaphenylene benzoxazole (PBO) fibers, polyphenylene sulfide fibers, polyester fibers, acrylic fibers, nylon fibers, and polyethylene fibers. These may be used alone or in combination of two or more. The reinforcing fibers may be surface-treated with a silane coupling agent or the like in order to enhance adhesion to the polymer layer formed from the present dispersion. Among these, glass fiber, aramid fiber and carbon fiber are preferred, and from the viewpoint of electrical insulation, plain-woven glass fiber fabric made of electrically insulating E-glass yarn defined in JIS R 3410 is particularly preferred.

[0040] The fiber substrate is preferably in the form of a sheet. For example, a cloth woven from reinforcing fiber bundles made of a plurality of reinforcing fibers, a substrate in which a plurality of reinforcing fibers are aligned in one direction, a stack of these, etc. The reinforcing fibers do not need to be continuous over the entire length or width of the reinforcing fiber sheet, and may be broken along the way. The reinforcing fibers are preferably continuous long fibers having a length of 10 mm or more. The reinforcing fibers do not need to be continuous over the entire length or width of the reinforcing fiber sheet, and may be interrupted along the way.

[0041] The method of impregnating the fiber substrate with the present dispersion includes a method of immersing the fiber substrate in the present dispersion and a method of applying the present dispersion to the fiber substrate. The number of immersions in the former method and the number of applications in the latter method may be one or more. The fiber substrate impregnated with the dispersion is dried to remove at least a portion of the liquid medium. Drying can be carried out at a temperature of, for example, 80 to 120°C. Next, the F polymer is calcined by heating in a temperature range above the melting temperature of the F polymer, to obtain a prepreg having a polymer layer containing the F polymer on the surface and inside of the fiber substrate. Specifically, the heating for calcining the F polymer is preferably performed at 340 to 400°C for 0.1 to 30 minutes. In the prepreg, the F polymer derived from the F particles does not need to be fully melted as long as the shape of the prepreg is maintained. Such a prepreg can be used as a molding material, and a molded body can be produced by heating and pressing. The drying of the fiber substrate impregnated with the dispersion and the calcination of the F polymer by heating may be carried out in one step.

[0042] After the heating for baking the F polymer, the temperature is lowered at a rate of less than 5° C. / min to at least the melting temperature of the F polymer, thereby obtaining a prepreg. The cooling rate is preferably 5° C. / min or more. From the viewpoint of further promoting the above-mentioned assumed mechanism and further achieving the effects of the present invention, it is preferable to maintain a cooling rate of less than 5° C. / min until the temperature reaches at least [melting temperature of F polymer−10° C.] after the heating, it is more preferable to maintain a cooling rate of less than 5° C. / min until the temperature reaches [melting temperature of F polymer−60° C.], and it is even more preferable to maintain a cooling rate of less than 5° C. / min until the glass transition temperature of F polymer. The temperature drop rate can be controlled, for example, by using a temperature control function associated with the above-mentioned oven or ventilated drying furnace as the heating device. For example, after maintaining a cooling rate of less than 5°C / min to at least [the melting temperature of the F polymer - 10°C], the prepreg can be obtained by allowing the material to cool in the air without any particular control of the cooling temperature, or by appropriate cooling such as water cooling. More specifically, it is preferable to maintain a temperature drop rate of less than 5° C. / min from [melting temperature of F polymer−10° C.] to [melting temperature of F polymer−60° C.]. The total content of PTFE and F polymer in the prepreg is preferably 30 to 80% by mass.

[0043] The prepreg as a molded product obtained by this method is formed by impregnating a fiber substrate with the dispersion, disposing the fiber substrate in the dispersion, heating the fiber substrate, and lowering the temperature as described above. This series of steps may be repeated two or more times. Alternatively, a prepreg may be formed by impregnating a fiber substrate with the present dispersion or by coating and disposing the present dispersion on the surface of the fiber substrate, removing the liquid medium by drying, and then further impregnating or coating the fiber substrate with the present dispersion and disposing and drying the same, and then heating the fiber substrate to sinter the F polymer, followed by cooling the fiber substrate at a rate of less than 5°C / min to at least the melting temperature of the F polymer or lower. Alternatively, the present dispersion may be placed on a fiber substrate, the F polymer may be sintered by heating, the present dispersion may be placed on the fiber substrate again, the F polymer may be sintered again by heating, and after the heating for the second sintering of the F polymer, the temperature may be lowered at a rate of less than 5°C / min to at least the melting temperature of the F polymer to form a prepreg.

[0044] The prepreg obtained by this method has a fibrous (fabric-like) surface property based on PTFE, and has high surface smoothness, and is also excellent in adhesion between the polymer layer and the fiber substrate, bending resistance, etc. The resin-coated metal foil obtained by thermocompression bonding such a prepreg and metal foil has high peel strength and is resistant to warping, and is therefore suitable for use as a printed circuit board material. In addition, by disposing the fiber substrate impregnated with the present dispersion on a part of the inner wall surface of a substrate that is a molded product such as a tank, a pipe, or a container, heating the substrate, and then cooling the substrate at a specific temperature drop rate by the present method, a fiber substrate layer containing PTFE and F polymer can be formed on the inner wall of the substrate that is a molded product. This method is also useful as a method for lining the inner wall surface of molded products such as tanks, pipes, and containers.

[0045] The thickness of the prepreg is preferably 1 to 3000 μm. In the case of use for printed circuit boards, the thickness of the prepreg is more preferably 3 to 2000 μm, and further preferably 5 to 1000 μm. The suitable ranges of the dielectric constant, dielectric tangent, thermal conductivity, and linear expansion coefficient of the prepreg are the same as those described above for the F layer.

[0046] Molded products formed by this method, such as laminates, prepregs, films or sheets, are useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, heat dissipation parts, and the like. Specifically, these include electric wire coating materials (aircraft electric wires, rectangular wires, FFC (Flexible Flat Cable), etc.), enameled wire coating materials used in motors for electric vehicles, etc., power generation coating materials, electrical insulating tapes, insulating tapes for oil drilling, oil transport hoses, hydrogen tanks, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), carrier films for fuel cells, tape base films for the semiconductor manufacturing process (dicing tape, pick-up tape, etc.), release films for semiconductor molding, liquid crystal antennas, reflectors, transmission lines, COF (Chip on Fuel) base films for electrostatic chucks for semiconductor manufacturing processes, electrostatic chucks for display manufacturing processes, copy rolls, furniture, automobile dashboards, covers for home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushes, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, food transport belts, etc.), tension ropes, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts for centrifugal pumps, chemical and water supply pumps, tools (shovels, files, drills, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, racket strings, dies, toilets, container coating materials, heat dissipation boards for mounting power devices, heat dissipation parts for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS They are useful as FETs, CPUs, heat dissipation fins, metal heat sinks, blades for wind turbines, wind power generation equipment, and aircraft, housings for personal computers and displays, electronic device materials, interior and exterior parts of automobiles, sealing materials for processing machines and vacuum ovens that perform heat treatment under low oxygen conditions, plasma processing equipment, heat dissipation parts in processing units for sputtering and various dry etching equipment, and electromagnetic wave shielding.

[0047] Molded products formed by this method, such as laminates, prepregs, films or sheets, are useful as electronic substrate materials such as flexible printed wiring boards and rigid printed wiring boards, protective films and heat dissipating substrates, particularly heat dissipating substrates for automobiles.

[0048] The present invention also relates to an adhesive molded article comprising polytetrafluoroethylene (PTFE) and a heat-fusible tetrafluoroethylene-based polymer (F polymer), the entire surface of which has substantially fibrous surface properties (hereinafter also referred to as "the adhesive molded article"). Here, "the entire surface has fibrous surface properties" means that when any 10 points on the surface of the adhesive molded article are observed with a scanning electron microscope (SEM), all of the points have a fibrous (fabric-like) surface based on PTFE, and the adhesive molded article has properties based on such surfaces. The details of the F polymer and PTFE in the present adhesive molding are the same as those of the F polymer and PTFE described above. The present adhesive molding is preferably formed by the present method. Specific examples of the present adhesive molding include the above-mentioned laminates having a polymer layer as a molding, and prepregs. Since the entire surface of the present adhesive molding has fibrous surface properties, it has a surface friction coefficient equivalent to that of PTFE, and is therefore likely to retain the low friction properties inherent to PTFE. The surface friction coefficient of PTFE refers to the dynamic friction coefficient measured in contact with a chrome-plated steel plate at room temperature in accordance with JIS K 7125.

[0049] Although the present method and the present adhesive molding have been described above, the present invention is not limited to the configuration of the above-mentioned embodiment. For example, the present method may have any other steps in addition to the configuration of the above-mentioned embodiment, or may be replaced with any other steps that produce the same effect. EXAMPLES

[0050] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [Heat-fusible F polymer particles] F particle 1: containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of TFE units, NAH units, and PPVE units, in that order, and having a carbonyl group-containing group with a main chain carbon number of 1×10 6Tetrafluoroethylene polymer particles (melting temperature: 300°C) with 1000 particles per particle (D50: 2.4 μm, Tg: 85°C, specific surface area: 9 m 2 / g) [Water dispersion containing PTFE particles] PTFE dispersion: Aqueous dispersion of PTFE containing 50% by mass of non-melt-processable PTFE particles (D50: 0.3 μm) [Surfactants] Surfactant 1: A nonionic surfactant having a polysiloxane chain in the main chain and a polyethylene oxide group in the side chain.

[0051] 2. Dispersion liquid production example [Production Example 1] (1) Using a planetary centrifugal mixer, F particles 1, surfactant 1, and water were mixed to prepare dispersion liquid a having an F particle 1 content of 33 mass % and a surfactant 1 content of 3 mass %. (2) Next, the PTFE dispersion and dispersion a were mixed to obtain dispersion 1 in which PTFE particles and F particles 1 were dispersed in water and the mass ratio of F particles 1 to PTFE particles was 0.2. [Production Example 2] The PTFE dispersion and the dispersion a obtained in Example 1(1) were mixed to obtain a dispersion 2 in which PTFE particles and F particles 1 were dispersed in water and the mass ratio of F particles 1 to PTFE particles was 0.33.

[0052] 3. Example of laminate production and evaluation [Example 1] The dispersion 1 obtained in Production Example 1 was applied to the surface of copper foil (thickness 18 μm) to form a coating layer, and the coating layer was dried by passing it through a ventilated drying oven at a furnace temperature of 100° C. for 10 minutes. Next, the F particles 1 were melted and sintered in a far-infrared oven at a furnace temperature of 380° C. under an inert gas atmosphere for 10 minutes to form a polymer layer on the surface of the copper foil, and then the temperature was lowered to 275° C. at a temperature lowering rate of 3° C. / min and further cooled to 25° C. to obtain a laminate 1 (resin-coated copper foil) in which a copper foil and a polymer layer (thickness 25 μm) containing PTFE and F polymer 1 were formed on the copper foil surface. Ten random points on the polymer layer surface of the laminate 1 were observed using SEM images (magnification: 30,000 times) and rated according to the following criteria, resulting in a rating of "A." In addition, the polymer layer surface formed a fibrous surface derived from PTFE, and the surface friction coefficient was equivalent to that of a layer of PTFE alone. <SEM image observation and evaluation of the molded layer surface> A: No uneven distribution of F polymer 1 (island-like areas) was confirmed at any of the 10 points. B: The uneven distribution of F polymer 1 is confirmed at any of the 10 arbitrary points.

[0053] [Example 2] Laminate 2 was obtained in the same manner as in Example 1, except that in Example 1, the temperature reduction rate after forming a polymer layer on the surface of the copper foil was 3°C / min up to 350°C, and then more than 5°C / min, and the copper foil was allowed to cool to 25°C. Ten random points on the surface of the polymer layer of the laminate 2 were observed using an SEM image (magnification: 30,000 times) and evaluated according to the following criteria, resulting in a rating of "B." In addition, the surface friction coefficient of the polymer layer was greater than that of a layer of PTFE alone. Furthermore, the peel strength between the polymer layer and the copper foil in the laminate 1 was 10 N / cm or more.

[0054] 4. Prepreg manufacturing examples and evaluation [Example 3] The dispersion 1 obtained in Production Example 1 was impregnated into a glass fiber woven fabric to form an impregnated layer, and the impregnated layer was passed through a ventilated drying oven at a furnace temperature of 100 ° C for 10 minutes to dry. Next, the F particles 1 were melted and fired by heating in a far-infrared oven at a furnace temperature of 380 ° C for 10 minutes under an inert gas atmosphere, and then the temperature was lowered to 275 ° C at a temperature drop rate of 3 ° C / min, and further cooled to 25 ° C. The operation of impregnating the dispersion 1 into the glass fiber woven fabric, drying, firing, and temperature drop was repeated a total of four times under the same conditions. Thereafter, the PTFE dispersion was further impregnated and dried at 100 ° C for 10 minutes, heated at 380 ° C for 10 minutes under an inert gas atmosphere, cooled to 275 ° C at a temperature drop rate of 5 ° C / min, and further cooled to room temperature. As a result, a prepreg 1 in which a polymer layer containing PTFE and F polymer 1 was formed on the glass fiber woven fabric was obtained. When the surface of prepreg 1 was observed using an SEM image (magnification: 30,000 times), a fibrous surface derived from PTFE was formed, and the surface friction coefficient was equivalent to that of PTFE.

[0055] [Example 4] Prepreg 2 was obtained in the same manner as in Example 3, except that the temperature drop rate was 3°C / min up to 350°C, and then increased to more than 5°C / min and cooled to 25°C. The bending property of prepreg 1 was superior to that of prepreg 2. [Industrial Applicability]

[0056] The laminates, prepregs and other molded products obtained by this method exhibit the surface properties based on PTFE and the properties of the F polymer to a high degree, and are dense and less susceptible to cracking, as well as excellent adhesion, heat resistance and electrical properties, making them effective for a variety of applications such as printed circuit boards.

Claims

1. A method for producing a molded product, comprising disposing a dispersion liquid containing polytetrafluoroethylene particles, particles of a heat-fusible tetrafluoroethylene-based polymer, and a liquid medium, and heating the dispersion liquid in a temperature range above the melting temperature of the tetrafluoroethylene-based polymer to obtain a molded product containing the polytetrafluoroethylene and the tetrafluoroethylene-based polymer, the method comprising the steps of: After the heating, the temperature is lowered at a rate of less than 5° C. / min to a temperature not higher than the melting temperature of the tetrafluoroethylene-based polymer.

2. The method according to claim 1, wherein the melting temperature of the tetrafluoroethylene-based polymer is 230 to 320°C.

3. The method according to claim 1 , wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer having a carbonyl group-containing group.

4. The method according to claim 1, wherein the average particle size of the polytetrafluoroethylene particles is 0.01 to 10 μm, the average particle size of the tetrafluoroethylene-based polymer particles is 0.05 to 50 μm, and the average particle size of the former is equal to or smaller than the average particle size of the latter.

5. The method according to claim 1 , wherein the content of the tetrafluoroethylene-based polymer particles in the dispersion is 5% by mass or more relative to the polytetrafluoroethylene particles.

6. The method according to claim 1, wherein after the heating, the temperature-reducing rate of less than 5° C. / min is maintained to at least [the melting temperature of the tetrafluoroethylene-based polymer−10° C.].

7. The method according to claim 1 , wherein the dispersion further comprises a surfactant.

8. The method according to claim 1 , wherein the dispersion further contains an inorganic filler.

9. The method according to claim 1 , wherein the liquid medium is at least one selected from the group consisting of water, amides, ketones and esters.

10. The method according to claim 1 , wherein the dispersion is applied and disposed on a surface of a substrate to form a laminate having a substrate layer and a polymer layer.

11. The method of claim 10, wherein the polymer layer has a thickness of 25 μm or more.

12. The method of claim 1 , wherein the dispersion is disposed on a fibrous substrate by impregnation to form an impregnated substrate in which the fibrous substrate is impregnated with the polymer.

13. An adhesive molded article comprising polytetrafluoroethylene and a heat-fusible tetrafluoroethylene-based polymer, the adhesive molded article having substantially the entire surface with fibrous surface properties.

Citation Information

Patent Citations

  • Powder dispersion liquid, laminate, film, and impregnated woven fabric

    WO2020004339A1